Destruction of zirconium nitride coatings formed by reactive magnetron sputtering under tensile loads - Kotov, Sergey Yu.; Frolov, Igor S. (Journal of the Belarusian State University. Physics, 2026)
The crack-resistant properties of coatings formed by reactive magnetron sputtering on bearing steel bases are considered. The features of destruction of zirconium nitride coatings with thicknesses of 0.3 – 0.7 μm on flat bases made of structural bearing steel grade ShKh15 (GOST 801-78) under uniaxial tension conditions are presented. It has been shown that, under tensile loads leading to a relative elongation of samples by 0.1– 20.0 %, no signs of peeling or chipping were detected on the surface of zirconium nitride coatings with thicknesses of up to 0.7 μm. The occurrence of the first cracks directed perpendicular to the tensile load were detected in a coating with a thickness of 0.7 μm was established at a relative elongation of the sample of 0.5 %, while in a coating with a thickness of 0.3 μm, the formation of cracks begins at a relative elongation of the sample of 3.0 %. The results of diffractometric studies of the structural features and magnitude of residual stresses of a zirconium nitride coating formed by reactive magnetron sputtering are presented. It has been established that the zirconium nitride coatings with a thickness of 0.3 – 0.7 μm formed by reactive magnetron sputtering on flat bases made of structural bearing steel grade ShKh15 under uniaxial tension conditions has high crack-resistant properties, which proves the feasibility of their use in rolling friction units.